Level of Coastal Protection Damage and Priority of Handling (Case Study of Alue Naga – Neuheun, Aceh Besar, Indonesia) - Syahrul Mauluddin; Ella Meilianda; Syamsidik Syamsidik (TDMRC, Universitas Syiah Kuala, 2019)
The massive tsunami of December 26, 2004 has had a huge impact on the life of the coastal region. The effects of the tsunami caused damage to occupation settlements, loss of waterside land and destruction of marine biota ecosystems. The coastal region of Aceh Province in Indonesia is the area that has the worst impact followed by the State of Malaysia, Thailand and as a coastal area of India. As a result of a large amount of coastal land experiencing a loss of land mass, erosion is very significant. As a step towards handling coastal areas from greater erosion prevention, the Government of Indonesia in 2005 adopted a policy of handling rehabilitation and reconstruction through the ANTERP (Aceh Nias Tsunami and Earthquake Response Program) program under the BRR (Rehabilitation and Reconstruction Agency) in collaboration with Ministry of Public Work. One of the steps to handling erosion is to protect the coast using the hard structure method such as the construction of a revetment and jetty made from rock armor. This study aims to assess the level of damage and priority of handling of coastal protective structures that have been built in 2009, 2016 and how changes in shoreline occur on the beach location of Alue Naga - Neuheun, which is a coastal area that was greatly affected by the tsunami. Assessments were carried out in three different coastal structures, namely CS-1 locations in the Alue Naga area, CS-2, Lambada Lhok coastal area and CS-3 Neuheun beach area. Guidelines for assessing structure damage and changes in shoreline in the study using the Ministry of Public Work Regulation No. 08/SE/M/2010. The rate of change in shoreline is obtained through computational calculations of the DSAS (Digital Shoreline Analysis System) program using the EPR (End Point Rate) method and NSM for change distance (Net Shoreline Movement).